At the Border: Malaysian Poets Dismantling Fences: (Di Sempadan: Penyair Malaysia Meruntuhkan Pagar) (Malay Literature, 2015)
The corpus of Malaysian literature representing Indonesia is quite large. From this corpus, the study chooses poetry as its genre. Applying the border aesthetics project of the Arctic University of Norway, it investigates how changing perceptions of borders relate to shifting practices of aesthetic evaluation. Two major poets who have lived and studied in Indonesia and returned are chosen. They are Baha Zain, who studied at Universitas Indonesia between 1970-1972, and Siti Zainon who studied in ASRI Jogja (1972-1974) and later lived and researched in Aceh. Both poets have written poems about Indonesia from fresh experiences or used these as vehicles into themselves. Their works were more dynamic, more thoughtful and benefitted from a comparative stance. Their language was enriched and became more colourful. Though what they experienced may be described as difficult, the final analysis, they portray themselves as friends of the country, since they participated and became part of its life and tragedies. They grew and matured with Indonesia. And it is through these many quite exceptional experiences that they interlinked the  history, literatures, and writers of Indonesia and Malaysia.Keywords: Malaysian poet, border aesthetic, Baha Zain, Siti Zainon Ismail, Indonesia, Malaysia